2021
DOI: 10.1152/ajpgi.00099.2021
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and renin-angiotensin system: a complex interplay at local and systemic levels

Abstract: Gut microbiota is a potent biological modulator of many physiological and pathological states. The renin-angiotensin system (RAS), including the local gastrointestinal RAS (GI RAS), emerges as a potential mediator of microbiota-related effects. The RAS is involved in cardiovascular system homeostasis, water-electrolyte balance, intestinal absorption, glycemic control, inflammation, carcinogenesis and aging-related processes. Ample evidence suggests a bidirectional interaction between the microbiome and RAS. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 160 publications
(155 reference statements)
2
46
0
Order By: Relevance
“…In the high-fructose diet plus 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure model, 3,3-dimethyl-1-butanol (DMB) therapy protected against hypertension coinciding with decreased AT1R and increased AT2R protein abundance [ 11 ]. Emerging evidence suggests a bidirectional interaction between the gut microbiome and RAS; gut microbiota-derived metabolites can modulate the gut RAS, while alterations in RAS shape microbiota composition and metabolic activity [ 64 ]. Considering maternal fructose consumption altered gut microbiota and the RAS concurrently, more work is required to explore the interaction between gut microbiome and the RAS implicating the pathogenesis of fructose-induced developmental programming.…”
Section: Fructose and Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…In the high-fructose diet plus 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure model, 3,3-dimethyl-1-butanol (DMB) therapy protected against hypertension coinciding with decreased AT1R and increased AT2R protein abundance [ 11 ]. Emerging evidence suggests a bidirectional interaction between the gut microbiome and RAS; gut microbiota-derived metabolites can modulate the gut RAS, while alterations in RAS shape microbiota composition and metabolic activity [ 64 ]. Considering maternal fructose consumption altered gut microbiota and the RAS concurrently, more work is required to explore the interaction between gut microbiome and the RAS implicating the pathogenesis of fructose-induced developmental programming.…”
Section: Fructose and Gut Microbiotamentioning
confidence: 99%
“…The SCFAs have been used as postbiotics as they are fermentation products of polysaccharides by gut microbiota [ 64 ]. So far, there is only one report showing that maternal high-fructose diet-induced hypertension can be protected by acetate supplementation [ 41 ].…”
Section: Reprogramming Strategies Targeted On Gut Microbiotamentioning
confidence: 99%
“… 15 The presence of RAS and their local activity in the GIT have received pronounce attention lately; where many studies showed the involvement of local RAS in the gut in glycemic control and electrolyte regulation, besides having roles in carcinogenesis and inflammatory reactions. 16 Studies showed that blocking angiotensin II receptor AT1 protect against gastric ulcer, 17 , 18 since angiotensin II can generate reactive oxygen species with inducing inflammatory reaction and cellular damage. These effects are mainly mediated through mucosal vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
“…The intestine is an essential homeostatic organ responsible for nutrient absorption and interaction with abundant gut microbiomes. Some key intestinal processes are regulated by the intestinal RAS, which plays a role in digestion, peptide transport, and water–electrolyte homeostasis [ 14 ]. The intestinal RAS is also a major regulator of glucose uptake in the intestines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%